Artisan/Practitioners and the Rise of the New Sciences, 1400-1600 - Long, Pamela O. (Book collections on Project MUSE., 2011)
"Explores the influence of craftsmen and practitioners such as farmers and navigators in the development of the new sciences during the period in the title"--